The Efektivitas Pembelajaran STEM dengan Pendekatan PjBL dalam Meningkatkan Pemahaman Relasional Matematis Siswa - Riyanto Dwi Saputra Anang; Alfira Mulya Astuti; Erpin Evendi (Jurnal of Math Tadris, 2025)
This study examined the effectiveness of STEM-based learning integrated with the Project-Based Learning (PjBL) approach in enhancing eighth-grade students’ relational mathematical understanding at SMP Negeri 1 Batukliang during the 2025/2026 academic year. A quantitative approach with a quasi-experimental method employing a pretest–posttest control group design was used. The population comprised all eighth-grade students of SMP Negeri 1 Batukliang (206 students). Using purposive sampling, two classes were selected: Class VIII3 as the control group and Class VIII4 as the experimental group, involving a total of 56 students. Data were collected through an essay-type test measuring relational mathematical understanding, administered at the pretest and posttest stages. Data analysis employed descriptive and inferential statistics using SPSS version 27, including normality and homogeneity tests, N-Gain analysis, and an Independent Samples t-test. The results showed that the average N-Gain score of the experimental class was 0.4906 (moderate category), which was higher than that of the control class at 0.2889 (low category). Furthermore, the t-test revealed a significance value of 0.000 (< 0.05). These findings indicate that STEM-based learning integrated with the PjBL approach is effective in improving students’ relational mathematical understanding.